Binding Pattern Reconstructions of FGF-FGFR Budding-Inducing Signaling in Reef-Building Corals - Guo, Zhuojun; Liao, Xin; Chen, J.-Y.; He, Chunpeng; Lu, Zuhong (Frontiers in Physiology, 2022)
Reef-building corals play important role in marine ecosystems, and are declining under the influence of climate change, ocean acidification and invasive crown-of-thorns starfish predation. As marine animals composed of polyps, reproduction by asexual budding is pivotal in scleractinian coral growth. The fibroblast growth factor (FGF) signaling pathway is essential in coral budding morphogenesis. Here, we sequenced the full-length transcriptomes of four common and frequently dominant reef-building corals and screened out the budding-related FGF and FGFR genes. Then, three-dimension (3D) models of FGF and FGFR proteins as well as FGF-FGFR binding models were reconstructed. Our research reveals that the FGF8-FGFR3 binding models in Pocillopora damicornis, Montipora capricomis and Acropora muricata are typical receptor tyrosine kinase-signaling pathways similar to the Kringelchen (FGFR) in hydra. However, in P. verrucosa, FGF8 is not the FGFR3 ligand, as in other hydrozoan animals, and its FGFR3 must instead be activated by other tyrosine kinase-type ligands. This work suggests a budding propagation signaling pathway background in reef-build corals that could potentially help in the restoration of coral reefs in the future.